أثر أبعاد إدارة الموارد البشرية الخضراء في تعزيز سمعة المنظمة (دراسة تحليلية لآراء عينة من القيادات الأدارية في الجامعات الحكومية في مدينة السليمانية) - رشيد, نيان كمال; صالح, رازاو رشيد (Sulaimani Journal for Humanities, 2022)
This study aims in detecting relation between green Human resource management with its dimensions (green adaptation, training and development in green ,evaluation of green manifestation ,preserving of energy)and he reputation of the organization its (invention ,social responsibility ,quality and service aspects). The problem : this research came up to existence from a question ever posed like :what is t effects of management of administering Green Human resources and the reputation of the organization ,and subsidiary questions like : what is the nature of the dashing away management human green resources And the reputation of the organization Perceived in the studied universities 2- what are the effects of excluding Green Human resource Management in supporting the reputation of the organization in the studies university , ? The researcher has used the description analytical method seeking to gain the aims of the study and answering the former questions ,she has used a virtual example in reflecting the nature of the relation and effects between the Study variables and their dimensions depending on sum main and subsidiary hypothesis that were subjected to sum statistical tests through statistical for social sciences (SPSS.v.26)the study society included the leaderships of government universities in Sulaimaniyah City and used questionnaires as a basic tool to collected data and information distributed on a management staff in the so named universities about 150 questionnaires forms from which 120 were taken back good enough to be analyzed. The main results were : The results of the study confirmed the existence of a strong correlation between the two variables and their dimensions at the macro and micro level, and this confirms that the greater the interest of the researched universities in green human resources, the stronger the organizational reputation.Suggestions : to push the employees to hold and create friendly o environment dimensions while they were in the organization or outside of it ,like encouraging common transport while coming to the organization and restricting usage of electric and power ,few printing.
Keywords: Green Human resources Management; Perceived organizations reputation; government universities